The Construction of Efficient Portfolios: A Verification of Risk Models for Investment Making - Gültekin, Mustafa N.; Shohfi, Thomas D.; Guerard, John B. (Frontiers in Applied Mathematics and Statistics, 2020)
Statistical risk models have been estimated since the mid-1960s. One can argue how many factors are necessary, but there appears to be substantial evidence that statistical models outperform fundamental models for several expected returns models, such as we test in this analysis. In this paper, we show that tracking portfolios constructed with expected return rankings based on earnings forecasting and price momentum composite alpha strategies produce statistically significant excess returns and increased Sharpe Ratios when optimized with 3-factor statistical risk model.